Status of Indoor Air Pollution in Tanzania, a Review (The Journal of Building and Land Development, 2018)
Indoor air pollution is one of the existing global environmental problems. Its impacts seem to be more apparent in developing countries but unfortunately the information about the magnitude of the problem is scarce. Depending on the type of pollutants and the exposure duration, indoor air pollutants cause significant damage to public health. Among the several known sources, use of biomass for cooking has been reported to be the major contributor of indoor air pollution. For developing countries, it follows in this case that women and children who spend most of their times indoor are the most vulnerable group. Strategies to protect the public against the air pollutants need to be sought and implemented.In this paper general information on indoor air pollution, the magnitude of the problem globally and in developing countries, as well as the general situation in Tanzania are reported. Further information for Tanzania especially on the risk behaviours leading to indoor air pollution, the possible techniques that can be employed to reduce the magnitude of the problem and areas for further research are pointed out. The need for more research to inform the policy and decision making processes is underscored. Research areas to be pursued for generating knowledge to help the decision maker and the public in general on the best ways to reduce indoor air problems are specified.Keywords: Indoor air pollution, biomass energy, cooking, developing countries, Tanzania